DAYA TERIMA DAN KANDUNGAN GIZI SEREAL YANG DISUBSTITUSI DENGAN TEPUNG BUAH LINDUR (Bruguiera gymnorrizha) DAN TEPUNG JAGUNG (Zea mays) - Erfyna Girsang; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
People’s still do not know that lindur (Bruguiera gymnorrizha) can be processed into some variety of foods, such as cereals. The purpose of this research is to determine the people acceptibility and nutrient composition of cereals that was substituted with fruit flour lindur (Bruguiera gymnorrizha) and corn starch (Zea mays). This research was an experiment to produce cereals with the addition of lindur starch and corn starch with the comparison composition was (30% : 70%) and (40% : 60%). Research about cereals acceptibility test was held at the Public Health Faculty, University of North Sumatra, with 30 panelists and the analysis of cereals nutrient composition was carried out in the Laboratory of Industrial Standardization Research Board of Medan. Data analysis was processed using Wilcoxon Signed-Rank test and elaborated by percentage descriptive. Results of research using organoleptic test to color, aroma, flavor, and cereals texture that was substituted by lindur fruit flour and corn flour with composition 30% : 70% contributed 18.6% protein, 19,7 fat and 58,4 carbohydrate in 100 grams of ingredientsl. Composition of 40% : 60% contributed 18.0% protein, 20% fat and 53.1% carbohydrate in 100 grams of ingredients. Results of Wilcoxon Signed-Rank test showed that there are differences in acceptibility of color (0,001) and flavor (0.022). There are no differences in acceptibility of aroma (0.841) and texture (0,467)of cereals. This research suggests that for lindur can be used for producing cereals as a healthy snacks, low cost or cheap as well as being a substitution for flour that is always used for foods and rich in nutrient that is good for foods. Keywords: Cereals, Lindur Starch , Corn Starch, Acceptibility, Nutritient Composition